Legal Liability of Business Operators For Beauty Products Containing Hazardous Chemicals - Elvia Rahmawati; Miftakhul Huda; Ian Firstian Aldhi (Journal of Law, Politic and Humanities, 2024)
This study aims to analyse the liability of business operators for beauty products containing hazardous chemicals. This normative legal research employs methods including a statutory approach to examine relevant laws and a case-based approach to analyse real life instances of non-compliance. Findings reveal that despite strict regulations, enforcement challenges persist, leading to potential health risks for consumers. The study emphasizes the legal responsibilities of business operators to compensate for damages caused by non-compliant products, as outlined in Law No. 8 of 1999 on Consumer Protection. The research concludes that the resolution of consumer dispute cases can be settled through the Consumer Dispute Settlement Agency (BPSK) in three stages: mediation, conciliation, and arbitration, where the decisions made are final and binding. Besides resolution through BPSK, consumer dispute cases can also be resolved through litigation, which typically incurs more costs and takes more time compared to resolution through BPSK. Alongside proactive consumer actions to report hazardous products to regulatory bodies. This comprehensive approach ensures consumer safety and upholds legal standards within the beauty industry.